Regional zircon U-Pb geochronology for the Maniitsoq region, southwest Greenland - Olierook, Hugo Kees Herman; Kirkland, Christopher L; Hollis, Julie A; Gardiner, Nicholas; Yakymchuk, Chris; Szilas, Kristoffer; Hartnady, Michael; Barham, Milo; McDonald, Bradley; Evans, Noreen; Steenfelt, Agnete; Waterton, Pedro (figshare, 2021)
Supplementary dataset to Olierook et al., Scientific Data.